Structure and nodal points of Smart City infrastructure - Magdalena Grochulska-Salak; Tomasz Wężyk (Acta Scientiarum Polonorum. Architectura)
The development of Smart City systems and infrastructure should provide an implementation of assumptions for harmonious and sustainable development of urban areas. Implementation of Smart City assumptions within the city structure is related to introduction and development of passive and inert infrastructure that constitutes elements of the city infrastructure, as well as particular form of development of areas and buildings. The following research work concerns an analysis of spatial and infrastructure-related solutions as well as environmental, social and ICT systems applied within the city. Source material analyses (urban, architectural and technological sources) provide the basis for conclusions and formulation of typology and implementation of criteria for smart urban, social and ecosystem-related infrastructure implemented in the Smart City model, with the use of innovations in the field of intelligent information and communication technologies (ICT) as well as network infrastructure. The conclusions derived from the following research work contribute to the discussion on ways to shape the structure of infrastructure and nodal points in the Smart City development model in relation to sustainable development issues.